2021
DOI: 10.3389/fcell.2021.653808
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA KCNQ1OT1 Secreted by Tumor Cell-Derived Exosomes Mediates Immune Escape in Colorectal Cancer by Regulating PD-L1 Ubiquitination via MiR-30a-5p/USP22

Abstract: Background: This study tried to explore the mechanism of long non-coding RNA (lncRNA) KCNQ1OT1 in tumor immune escape.Methods: Gene Expression Omnibus (GEO) and microarray analysis were used to screen the differentially expressed lncRNA and microRNA (miRNA) in normal tissues and tumor tissues. Quantitative reverse transcription PCR (RT-qPCR) was used to quantify KCNQ1OT1, miR-30a-5p, ubiquitin-specific peptidase 22 (USP22), and programmed death-ligand 1 (PD-L1). The interactive relationship between KCNQ1OT1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 44 publications
0
39
0
1
Order By: Relevance
“…Exosomes derived from pancreatic cancer (PaCa) cells had high levels of miR-212-3p, which inhibited the expression of regulatory factor X-associated protein (RFXAP), resulting in a decrease in the expression of MHC II molecules and inducing immune tolerance [ 50 ]. Xian et al found that the tumor-promoting effect of the lncRNA KCNQ1OT1 occurred through autocrine effects of colorectal cancer cell-derived exosomes (CRC-Exos), which mediated the miR-30a-5p/USP22 pathway to regulate the ubiquitination of PD-L1 and inhibit the CD8+ T-cell response, thereby promoting colorectal cancer development [ 51 ]. Growing evidence links tumor progression with the activity of various immune cells, such as macrophages.…”
Section: Cancer-promoting Effects Of Csc-exosmentioning
confidence: 99%
“…Exosomes derived from pancreatic cancer (PaCa) cells had high levels of miR-212-3p, which inhibited the expression of regulatory factor X-associated protein (RFXAP), resulting in a decrease in the expression of MHC II molecules and inducing immune tolerance [ 50 ]. Xian et al found that the tumor-promoting effect of the lncRNA KCNQ1OT1 occurred through autocrine effects of colorectal cancer cell-derived exosomes (CRC-Exos), which mediated the miR-30a-5p/USP22 pathway to regulate the ubiquitination of PD-L1 and inhibit the CD8+ T-cell response, thereby promoting colorectal cancer development [ 51 ]. Growing evidence links tumor progression with the activity of various immune cells, such as macrophages.…”
Section: Cancer-promoting Effects Of Csc-exosmentioning
confidence: 99%
“…Additionally, KCNQ1OT1 expression is upmodulated in methotrexate-resistant colorectal cancer cells, and KCNQ1OT1 silencing re-sensitizes resistant cells to methotrexate through downregulating cAMP-response element binding protein (CREB) and CREB-binding protein (CBP) levels [146]. Of late, KCNQ1OT1 was observed to support ubiquitin-specific peptidase 22 (USP22)-mediated stabilization of PD-L1 by deactivating miR-30a-5p and thereby inhibiting the anti-cancer immunity of CD8+ T cells [127]. Since KCNQ1OT1 is secreted from cancer cells via exosomes, the reciprocal transfer of KCNQ1OT1 between cancer cells can substantially increase PD-L1 levels, contributing to immune evasion [127] (Figure 4 and Table 2).…”
Section: Linc02418mentioning
confidence: 99%
“…Of late, KCNQ1OT1 was observed to support ubiquitin-specific peptidase 22 (USP22)-mediated stabilization of PD-L1 by deactivating miR-30a-5p and thereby inhibiting the anti-cancer immunity of CD8+ T cells [127]. Since KCNQ1OT1 is secreted from cancer cells via exosomes, the reciprocal transfer of KCNQ1OT1 between cancer cells can substantially increase PD-L1 levels, contributing to immune evasion [127] (Figure 4 and Table 2). KCNQ1OT1 knockdown may activate other oncogenic factors, since miR-30a-5p is intriguingly capable of negatively regulating tumor-suppressive genes [147,148].…”
Section: Linc02418mentioning
confidence: 99%
“…Xian’s group found that lncRNA KCNQ1OT1 derived from CRC cells can promote CRC progression. Mechanistically, exosomes can transfer KCNQ1OT1 via autocrine to mediate the miR-30a-5p/USP22 pathway, then regulate the ubiquitination of PD-L1 and inhibit CD8 + T-cell responses ( Xian et al, 2021 ). Taken together, these results suggested that dysregulated exosomal lncRNAs may be meaningful biomarkers for cancer cell proliferation.…”
Section: Biological Roles Of Exosomal Lncrnas In Gastrointestinal Cancermentioning
confidence: 99%